Patient-specific tube-voltage selection at coronary CT angiography based on the combination of X-ray attenuation on scout views and body mass index: how can appropriate radiation dose be achieved?. (October 2015) - Noto, Daichi; Funama, Yoshinori; Utsunomiya, Daisuke; Oda, Seitaro; Yuki, Hideaki; Yamashita, Yasuyuki
Background: Body weight, body mass index (BMI), and scout X-ray radiographic attenuation can be used to predict image noise on computed tomographic coronary angiography (CTCA) images. Purpose: To use a formula to predict patient-specific image noise and then select an appropriate CTCA patient-specific tube voltage for better radiation control. Material and Methods: Forty-eight patients who underwent CTCA imaging at 120 kVp were reviewed, and their patient information and scouting X-ray radiographic attenuations were recorded to identify the best correlations between patient data and image noise and to develop a predicted image noise formula. Subsequently, 54 patients subjected to scanning at 100 or 120 kVp, depending on the noise predicted by our formula, were prospectively studied. Two radiologists visually assessed the image quality of the right coronary artery (RCA), left anterior descending artery (LAD), and left circumflex artery (LCX) by consensus readings. Results: The predicted image noise = 0.939 BMI + 0.025 scouting attenuation + 20.16. The median value of the overall image noise was 30.55 HU at 120 kVp and 29.85 HU at 100 kVp. The mean visual evaluation scores at 100 and 120 kVp were 3.25 and 3.24 for the proximal RCA, 3.40 and 3.26 for the proximal LAD, and 3.30 and 3.15 for the proximal LCX, respectively. Conclusion: The BMI and scouting X-ray radiographic attenuation can be combined to predict the CTCA image noise. Our prediction formula is useful for deciding when to switch from the 120- to the 100-kVp technique.